Investigation of carbonation performance of polymer-phosphazene concrete using Taguchi optimization method - Tanyildizi, Harun (Elsevier Sci Ltd, 2021)
In this study, the effects of the curing time, the carbonation time, the phosphazene percentage used in the polymer and the cement content on the carbonation resistance of polymer-phosphazene concrete were experimentally and statistically investigated by Taguchi method. The Taguchi L-25 (5(6)) orthogonal table was selected for this study. 100 x 100 x 100 mm specimens were prepared. The specimens were cured in water at 20 +/- 2 degrees C for 28, 60, 90, 180 and 365 days. The polymer containing phosphazene was impregnated to the specimens and conducted polymerization by heating. Then, these samples were exposed to carbonation for 3, 7, 14, 28 and 56 days. The microstructure, the carbonation depth, ultrasonic pulse velocity, splitting tensile strength and changes in weight of the samples were determined. The Anova results found that cement content was found to be the experimental variable that most affected the results of the experiment. The percentage of this effect was found between 34.43% and 72.94% in Anova analysis. According to Taguchi results, the optimum experimental variables for the maximum splitting tensile strength, the maximum UPV, the minimum weight change and the minimum carbonation depth were found as 14 days for the carbonation time, 3% for the phosphazene percentage, 365 days for the curing time and 450 kg/m(3) for the cement content. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Polymer-phosphazene concrete; Carbonation; Microstructure; Mechanical properties